(untitled) (Clinics, 2012)
Neuroendocrine tumors are a heterogeneous group of malignancies that present a diagnostic challenge. The majority of patients (more than 60%) present with metastatic disease at diagnosis. The diagnosis is based on histopathology, imaging, and circulating biomarkers. The histopathology should contain specific neuroendocrine markers such as chromogranin A, synaptophysin, and neuron-specific enolase and also an estimate of the proliferation by Ki-67 (MIB1). Standard imaging procedures consist of computed tomography or magnetic resonance imaging together with somatostatin receptor scintigraphy. 68Ga-DOTA-octreotate scans will in the future replace somatostatin receptor scintigraphy because they have higher specificity and sensitivity. Other positron imaging tomographic scanning tracers that will come into clinical use are 18F-DOPA and 11C-5HTP. Neuroendocrine tumors secrete many different peptides and amines that can be used as circulating biomarkers. The most useful general marker is chromogranin A, which is both a diagnostic and prognostic marker in most neuroendocrine tumors. However, there is still a need for improved biomarkers for early detection and follow-up of patients during treatment. In addition, molecular imaging can be further developed for both detection and evaluation of treatment.